THE INFLUENCE OF COMPETENCY, MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE REGIONAL RESEARCH AND DEVELOPMENT AGENCY IN SOUTH SUMATERA PROVINCE - Mitha Putri Hartasih; Idris; Trihandayani; Achmad Ariandi (CV. Radja Publika, 2026)
Human Resources (HR) play an important role in organizations, as they act as managers of organizational systems. In order for these systems to function effectively, it is essential to pay attention to key aspects such as competence, discipline, education and training, as well as the level of work comfort. These factors encourage employees to contribute their full capabilities in accordance with organizational needs. The objectives of this study are: (1) to examine the influence of competence, motivation, and work discipline on the performance of employees at the Regional Research and Development Agency of South Sumatra Province; (2) to analyze the influence of competence on employee performance; (3) to determine the influence of motivation on employee performance; and (4) to identify the influence of work discipline on employee performance at the Regional Research and Development Agency of South Sumatra Province. This research employed a survey method with a quantitative approach by distributing questionnaires to employees of the Regional Research and Development Agency of South Sumatra Province, who also served as the population of the study. The data were analyzed using multiple linear regression analysis with SPSS version 24 for Windows. The results of the study indicate that: (1) competence, motivation, and work discipline simultaneously have a significant influence on employee performance; (2) competence has a significant influence on employee performance; (3) motivation has a significant influence on employee performance; and (4) work discipline has a significant influence on employee performance at the Regional Research and Development Agency of South Sumatra Province.